Analytic Hierarchy of Motivating and Demotivating Factors Affecting Labor Productivity in the Construction Industry: The Case of Azerbaijan - Aghayeva, Konul; Ślusarczyk, Beata (MDPI AG, 2019)
This research is aimed to identify and comparatively assess the motivation factors influencing labor productivity from the construction employees’ perception. Based on results of a filled-in and returned questionnaire distributed among 350 workers and managers from 25 construction companies throughout the Republic of Azerbaijan, motivation and demotivation factors were identified. The statistical analysis of motivation drivers showed that most important ones for all construction employees are remuneration (including its timely payment), job security, bonuses, and fringe benefits. Among top demotivators for all types of employees are unsafe work conditions, underpayment, and colleagues’ aggressive management style. Workers are also affected by bad treatment by managers and changing on workmates. While workers are more concerned with quality of site management and good relations with colleagues, managers are more motivated by responsible job and challenging tasks and demotivated by chaos and incompetent colleagues. Thus, according to the study, both economic and non-economic motivation and demotivation drivers occurred to be important for construction employees, and must be accounted by human resource (HR) officers. The results of the research would assist construction companies’ management in developing more precise and employee-oriented human resources strategies and policies.